Feasibility analysis of Pempek MSMEs processing business made from mackerel (Scomberomorus sp.) in the District Cileunyi Bandung Regency - -, junianto - (Agridevina : Berkala Ilmiah Agribisnis, 2024)
Culinary business "Pempek Dahsyat" managed at home. There are Pempek kapal selam, pempek lenjer, Pempek adaan, Pempek kulit ikan, and tekwan. The purpose of this study was to determine whether the business "Pempek Palembang Musi Raya", which is located on Jalan Kavling Mekar Biru No.213A, RT.01 / RW.07, Cibiru Hilir, District. Cileunyi, Bandung regency, West Java 40626, worthy to be established. The research was conducted through observation, interviews, and documentation. Legal analysis, marketing analysis, and environmental analysis were used. Business "Pempek Dahsyat" has been included and meets all aspects of the analysis so that this study can be considered feasible.